Integrating transcriptomic and proteomic analyses reveals impaired carbohydrate metabolism in tobacco cytoplasmic male sterility - Hou, Chaoliang; Liu, Yijie; Zhang, Yingjun; Wang, Ziqi; Cao, Yixiang; Tan, Can; Li, Qin; Ren, Zuohua; Zhou, Wei (Frontiers in Plant Science, 2025)
Cytoplasmic male sterility (CMS) is a vital tool for exploiting heterosis to enhance agricultural productivity. However, the genetic and molecular mechanisms of CMS in tobacco remain largely unclear. In this study, we used tobacco Gexin 3 CMS lines and their corresponding homozygous maintainer lines to systematically analyse the regulatory networks underlying CMS using transcriptomic, proteomic and morphological techniques. Morphological observations revealed premature stamen degeneration in CMS lines, resulting in failed self-pollination. Integrated transcriptomic and proteomic analyses identified 5,024 differentially expressed genes (DEGs) and 159 differentially expressed proteins (DEPs). Pathway enrichment analysis revealed that carbohydrate metabolism is a critical process in CMS. Several key enzymes, including hexokinase, pyrophosphate-fructose 6-phosphate 1-phosphotransferase and glyceraldehyde-3-phosphate dehydrogenase, were significantly downregulated at both the transcript and protein levels in the CMS lines. Reduced expression or functional impairment of these enzymes likely restricts the supply of substrates and ATP, thereby impairing floral and pollen development and ultimately reducing fertility. Network analysis identified several transcription factors as potential regulators of carbohydrate metabolism genes involved in floral organ development, including a CCCH-type zinc finger protein, an ethylene-responsive factor RAP2–4 and a LOB domain-containing protein. Taken together, these findings shed new light on the molecular basis of CMS in tobacco and lay the groundwork for exploring CMS regulatory networks in other crop species.